Nursing care for patients in post-transplantation of hematopoietic stem cells: an integrative review - Jéssica Alline Pereira Rodrigues; Maria Ribeiro Lacerda; Cristina Maria Galvão; Ingrid Meireles Gomes; Marineli Joaquim Meier; Nayla Tamara de Godoi Caceres (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the available evidence on the nursing care provided to patients after hematopoietic stem cell transplantation. Methods: integrative review with the search for primary studies in four databases and a virtual health library. A broad search strategy was used, including research published in English, Brazilian Portuguese, or Spanish, between 2008 and 2018, totaling a sample of 42 studies. Results: the studies were grouped into three categories: multiple nursing care (n=19), first-line care (n=18), and self-management of care (n=5). Conclusions: nursing care is critical, comprising patients' physical, psychological and social aspects. It occurs in hospital and home contexts, mainly involving technical actions and health guidance. The evidence identified provide subsidies for decision-making; however, most studies are of the non-experimental type, indicating the need for conducting intervention research.